EVOH nanocomposite films with enhanced barrier properties under high humidity conditions. Issue 4 (17th October 2013) - Kim, Dowan; Kwon, Hyok; Seo, Jongchul
<x xml:space="preserve">Abstract</x> To improve the oxygen and water vapor barrier properties of ethylene vinyl alcohol, EVOH/EFG nanocomposite films under high humidity conditions, we successfully prepared highly exfoliated graphite (EFG) containing a monolayer or a few layers of graphene via rapid heating treatment and ultrasonication as confirmed by Fourier transform infrared spectroscopy (FTIR), scanning electron microscope (SEM), elemental analysis (EA), and nitrogen adsorption–desorption analysis. Six different EVOH/EFG nanocomposite films containing as‐prepared EFG were prepared via a solvent blend method and their physical and barrier properties at different relative humidities were investigated as a function of EFG content. Depending on the EFG content, oxygen transmission rate (OTR) decreased from 3.7 to 0.1 cc/m2/day at dry condition, and the difference in OTR between dry condition and humid condition decreased from 6.5 to 2.3 cc/m2/day. Barrier properties of the EVOH/EFG nanocomposite films were strongly dependent on their chemical structure and morphology. Crystallinity, tortuous path length, and hydrophobicity of EVOH/EFG nanocomposite films were enhanced by the addition of EFG. However, the thermal stability and glass transition temperature of the nanocomposite films were not improved by incorporation of EFG due to the weak interaction between EVOH and EFG. To maximize the performance of EVOH/EFG nanocomposite films, the compatibility of the polymer matrix and fillers needs to be improved. POLYM. COMPOS., 35:644–654, 2014. © 2013 Society of Plastics Engineers